The impact of salinity perturbations on the future uptake of heat by the Atlantic Ocean. Issue 24 (20th December 2014) - Smith, Robin S.; Sutton, Rowan; Gregory, Jonathan M.
Abstract Anthropogenic ocean heat uptake is a key factor in determining climate change and sea level rise. There is considerable uncertainty in projections of freshwater forcing of the ocean, with the potential to influence ocean heat uptake. We investigate this by adding either −0.1 Sv (sverdrup (106 m3/s)) or +0.1 Sv freshwater to the Atlantic in global climate model simulations, simultaneously imposing an atmospheric CO2 increase. The resulting changes in the Atlantic meridional overturning circulation are roughly equal and opposite (±2 Sv). The impact of the perturbation on ocean heat content is more complex, although it is relatively small (∼5%) compared to the total anthropogenic heat uptake. Several competing processes either accelerate or retard warming at different depths. While positive freshwater perturbations cause an overall heating of the Atlantic, negative perturbations produce insignificant net changes in heat content. The processes active in our model appear robust, although their net result is likely model dependent and experiment dependent.